Mutual interference reduces offspring production in a brood- guarding bethylid wasp - Screenivas, A.G.; Hardy, Ian C.W. (Wiley, 2016)
Parasitoids have the potential to suppress populations of their hosts and thus may play an 2 important role in influencing the temporal and spatial dynamics of pest arthropods. 3 Behavioural interactions between foraging females, collectively constituting ‘mutual 4 interference’, can reduce host suppression. We use laboratory microcosms to assess the 5 prevalence and consequences of mutual interference behaviour in a bethylid wasp, Goniozus 6 nephantidis (Muesebeck) (Hymenoptera: Bethylidae), which is known to brood guard and to 7 engage in agonistic contests for individual hosts and which is also an agent of biological pest 8 control. We hold host and parasitoid numbers constant and vary the degree of female-female 9 contact that can occur. Mutual interference is manifest in a considerable reduction in the 10 number of offspring produced when females are not fully isolated from each other, due to 11 effects operating at the early stages of offspring production. This mutual interference may 12 contribute towards the limited degree of host population suppression achieved when some 13 species of bethylids are deployed as agents of biological pest control and also has clear 14 potential to influence the efficiency of mass rearing of parasitoids prior to field release.